Microwave assisted sol–gel synthesis of titanium dioxide using hydrochloric and acetic acid as catalysts - M. Andrade-Guel; L. Díaz-Jiménez; D. Cortés-Hernández; C. Cabello-Alvarado; C. Ávila-Orta; P. Bartolo-Pérez; P. Gamero-Melo (Boletín de la Sociedad Española de Cerámica y Vidrio, 2019)
Titanium dioxide (TiO2) was synthesized by microwave assisted sol–gel. The effect of the acid type used as catalyst on the phase transformation of TiO2 was investigated (hydrochloric or acetic acid). The samples obtained were characterized by scanning electron microscopy (SEM), this micrographs showed particles with irregular shapes. The results of Fourier transform-infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS) showed present signals of O and Ti. When hydrochloric acid was used as catalyst, three titania polymorphs were detected by X-ray diffraction (XRD), anatase, rutile and brookite, where the crystallite size was in the range of 9 and 16 nm. On the other hand, a single anatase phase was formed when acetic acid was used after only 15 min of reaction time. The anatase average crystallite size was obtained between 11 and 22 nm. Resumen: El dióxido de titanio (TiO2) se sintetizó mediante sol-gel asistido por microondas. Se investigó el efecto del tipo ácido utilizado como catalizador en la transformación de fase del TiO2 usando ácido clorhídrico o ácido acético. Las muestras se caracterizaron por microscopía electrónica de barrido (SEM), estas micrografías mostraron partículas de formas irregulares. Los resultados de la espectroscopia infrarroja de transformada de Fourier (FT-IR) y la espectroscopia de fotoelectrones de rayos X (XPS) mostraron signos de O y Ti. Cuando se usó ácido clorhídrico como catalizador, se detectaron tres polimorfos de titania por difracción de rayos X (XRD), anatasa, rutilo y brookita y el tamaño del cristalito estaba dentro del intervalo de 9 y 16 nm. Por otro lado, se formó una sola fase de anatasa cuando se usó ácido acético después de solo 15 min de tiempo de reacción. El tamaño de cristalito promedio de anatasa estaba dentro de 11-22 nm. Keywords: Titanium dioxide, Microwave-assisted sol–gel, Hydrochloric acid, Acetic acid, Palabras clave: Dióxido de titanio, Sol-gel asistido por microondas, Ácido clorhídrico, Ácido acético